2007
DOI: 10.1111/j.1537-2995.2007.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter pilot‐randomized controlled trial of the feasibility of an augmented red blood cell transfusion strategy for patients treated with induction chemotherapy for acute leukemia or stem cell transplantation

Abstract: BACKGROUND:Anemia may be an important factor contributing to an increased risk of bleeding, particularly in patients with thrombocytopenia. STUDY DESIGN AND METHODS:A multicenter, single-blinded pilot randomized controlled trial (RCT) was performed to evaluate the feasibility of conducting a larger RCT to determine the effect of the hemoglobin (Hb) concentration on bleeding risk. Patients with acute leukemia receiving induction chemotherapy or those undergoing stem cell transplantation were assigned to one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(156 citation statements)
references
References 73 publications
(159 reference statements)
3
153
0
Order By: Relevance
“…There were 4241 studies identified through our search, of which 14 were retrieved for full evaluation. Of the 14 articles retrieved for full-text review 6 studies involving 983 participants were included for the final review: 3 randomized controlled trials [3840] and 3 nonrandomized studies. [26, 27, 41]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 4241 studies identified through our search, of which 14 were retrieved for full evaluation. Of the 14 articles retrieved for full-text review 6 studies involving 983 participants were included for the final review: 3 randomized controlled trials [3840] and 3 nonrandomized studies. [26, 27, 41]…”
Section: Resultsmentioning
confidence: 99%
“…Three studies took place in the context of chemotherapy [38, 40, 41] and three studies were in the context of surgery. [26, 27, 39] Transfusion strategies were evaluated in several different types of cancer including leukemia,[40, 41] gastric,[38] colorectal,[26] hepatobilliary,[27] and mixed surgical oncology patients. [39] Two studies were conducted in the United States,[26, 27] one in Brazil,[39] one in Canada,[40] one in the Netherlands[41] and one in Korea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the RCTs are pilot studies [7][8][9][10][11][12][13] and another seven base their results on <200 patients per trial [14][15][16][17][18][19][20] and are probably too underpowered to explore differences in patient outcomes. Accordingly, they should be interpreted with caution.…”
Section: Relevant Clinical Outcomesmentioning
confidence: 99%
“…Four trials used a liberal Hb threshold of 9 g/dL (similar to the restrictive threshold in other trials). One RCT used a threshold of 11.3 g/dL, 32 another 12 g/dL, 8 and a third 13 g/dL. 17 A challenge of the trials was protocol adherence.…”
Section: Rbc Transfusion Thresholdsmentioning
confidence: 99%